Unusual demetalation of iron from [2]ferrocenophane skeleton of di‐nuclear ferracycle carbonyl complex. (17th January 2020) - Ji, Radhe Shyam; Tauqeer, Mohd.; Singh, Amrendra K.; Pathak, Biswarup; Shaikh, Mobin M.; Mathur, Pradeep
Abstract : Photolysis of a hexane solution containing 1, 1′‐ bis (trimethylsilylethynyl)ferrocene (1 ) and Fe (CO)5, under argon at 0 °C led to the formation of dinuclear complexes [Fe (CO)2 η 2 :η 2 – C (SiMe3 ) = C(C5 H4 )FeC(C5 H4 ) = C (SiMe3 )Fe (CO)3 –μ–CO] (2 ) and [Fe (CO)2 η 2 :η 2 –C (SiMe3 ) = C(C5 H5 )–C(C5 H5 ) = C (SiMe3 )Fe (CO)3 –μ–CO] (3 ). DFT calculations support the experimentally observed demetalation of ferrocene unit of 2 to 3 in presence of water. These compounds were comprehensively characterized by IR and 1 H and 13 C NMR spectroscopy and crystallographically (1 and 3 ). Abstract : High strain between the two cyclopentadienyl rings of complex 2 driven its conversion to the demetalated form complex 3 in presence of water on standing over a period of 5 hrs. Crystallographic and theoretical studies (HOMO‐LUMO gap)corroborate the release of strain as a factor for the demetalation observed.